Tantangan Sosial dan Pertumbuhan Transportasi Darat serta Kebijakan Pemerintah atas Transportasi Darat Berbasis Aplikasi Online - Yulianti Keke; Yuliantini Yuliantini; Veronica parhusip (Institut Transportasi dan Logistik Trisakti, 2019)
Increasing mobility of human activities requires transportation modes to be more reliable. The technology offered by online transportation service providers is a new technology in the transportation service industry which can grow rapidly. The technology offered also changes the way consumers use transportation services. This phenomenon also has a major impact on the transportation industry and requires the government to immediately improve regulations on transportation services. Along with consumer behavior that is increasingly digital and more dependent on the internet for daily activities such as information retrieval, shopping, and business transactions, making business both local and foreign begin to present online application-based transportation. The purpose of this study is to analyze and determine the social challenges of transportation and the drivers’ growth in online application-based transportation in Indonesia and their influence on government policy. The population was all application users based on online transportation, and obtained as many as 240 respondents gave responses to the questionnaire. Data were collected by interviews, questionnaires and documentation studies, variables studied using a Likert scale. The questionnaire was first tested using validity and reliability testing, analyzed by SEM analysis. The results found in the hypothesis testing of this study are: simultaneously, the social challenges of transportation and the growth of online application-based transportation have a positive and significant influence on government policy. Partially, the online application-based transportation challenge variables in Indonesia have a significant influence on government policy variables, so that they have a positive and significant influence. Partially, the online application-based transportation growth variable has a significant influence on government policy variables, so it has a positive and significant influence. Based on the 11 Goodness of Fit (GOF) criteria models above, the research model has a fairly good model. This means that the measurement model obtained from the data is in accordance with the research hypothesis. This is because of the 11 criteria, there are 8 criteria that have been fulfilled.